eVtols: smart air mobility project / Imran Hakimi Azman - Azman, Imran Hakimi (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
This abstract introduces a groundbreaking Smart Air Mobility Project tailored for Emergency Response Vehicles (ERV), utilizing Electric Vertical Takeoff and Landing (eVTOL) technology. Recognizing the urgent need for efficient emergency response, the project employs cutting-edge eVTOLs to overcome infrastructure constraints and enhance service delivery. ERV eVTOLs, electrically powered and AI-governed, ensure swift deployment independent of road networks. Advanced algorithms enhance response times, adapting dynamically to emergencies. Smart technologies enable real-time monitoring, data analytics, and adaptive route planning, fostering a responsive emergency ecosystem. Key features include a specialized charging infrastructure, seamless coordination with emergency services, and collaboration with regulatory bodies. The project envisions eVTOLs revolutionizing emergency medical services, search and rescue, and disaster relief, setting a new standard for agility and sustainability. By prioritizing collaboration with regulators, the project aims to establish safety protocols, ensuring the integration of eVTOLs into emergency response systems. In summary, the Smart Air Mobility Project for Emergency Response aims to transform emergency services, emphasizing the pivotal role of eVTOLs in ensuring rapid, sustainable, and effective response, ultimately enhancing the safety and well-being of communities in need.